(untitled) (Third Sector Social Economic Review, 2025)
In this research, it is aimed to determine the effect of consumers’ environmentally concious and simple consumption tendencies on their passenger car purchasing behavior. In line with this purpose; It is required to be 18 years or older and have experience in purchasing a car. In the research, snowball sampling method was used through Google forms, and data were collected through an online survey. According to the results of the statistical analysis; It has been concluded that while individuals prefer vehicles, they prioritize economic factors over environmental factors. So, an important findings revealed within the scope of the study; Nearly half of the consumers drive vehicles with diesel fuel, which is known to be more harmful to the environment, but is relatively economical. Moreover, consumers prefer manual transmission vehicles more than automatic transmission vehicles. According to another result, the priority is toward to electric and hybrid vehicles among vehicles with the same features and similar prices. In the study, there is a significant relationship between the the environmental conscious consumption scores of the consumers and “The situation of paying attention to the fact that the car to be purchased has features that cause less harm to the environment” and “priority preference in terms of fuel type between vehicles with the same features and similar prices”. There is also a significant relationship between consumers’ simple consumption scores and their passanger car buying behavior to gain social status and admiration.